Modularity of Orthopedic Implants 1997
DOI: 10.1520/stp12025s
|View full text |Cite
|
Sign up to set email alerts
|

Test Method for the Assessment of Fretting at the Femoral Head and Neck Taper Interface

Abstract: Today in the United States, 95% of all total hip implants contain at least one modular junction. The most common of these junctions connects the femoral head and neck taper. Because this connection utilizes a Morse taper, various materials and design variables can influence fretting and corrosion behavior at the mating surfaces, and ultimately the longevity of the device. In order to isolate and study the behavior of the femoral head/neck taper connection, a simplified model of a neck taper was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Several in vitro studies have been conducted on cyclically loaded modular prostheses to investigate the effects of mechanical loading on fretting and corrosion 8–23. Many researchers concluded that fretting could lead to corrosion due to disruption of the surface oxide 10, 12, 19, 24, 25.…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro studies have been conducted on cyclically loaded modular prostheses to investigate the effects of mechanical loading on fretting and corrosion 8–23. Many researchers concluded that fretting could lead to corrosion due to disruption of the surface oxide 10, 12, 19, 24, 25.…”
Section: Introductionmentioning
confidence: 99%
“…The search strategy is listed in Figure 1. The initial search yielded 1,224 unique articles. Ultimately, 91 articles remained for analysis (1-2-3, 8-9-10-11-12-13-14-15-16-17-18-19-20-21-22-23-24-25-26-27-28-29-30-31-32-33-34-35-36-37-38-39-40-41-42-43-44-45-46-47-48-49-50-51-52-53-54-55-56-57-58-59-60-61-62-63-64-65-66-67-68-69-70-71-…”
Section: Resultsmentioning
confidence: 99%